The Effectiveness of Massage Therapy on Reducing Low Back Pain in Pregnant Women - Astin Nur Hanifah; Rezqiqah Aulia Rahmat; Nuryani Nuryani (International Journal of Health Sciences, 2026)
Low back pain is one of the most common musculoskeletal complaints experienced by pregnant women, especially during the second and third trimesters. Anatomical changes, weight gain, altered body posture, and hormonal influences increase stress on the lumbar region, resulting in pain. Massage therapy is a widely used non-pharmacological intervention that improves blood circulation, relieves muscle tension, and promotes relaxation.To determine the effectiveness of massage therapy in reducing low back pain among pregnant women.This study employed a quasi-experimental one-group pretest-posttest design. Thirty pregnant women in the second and third trimesters with low back pain were recruited using purposive sampling. Massage therapy was administered for 20–30 minutes twice weekly for four weeks. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of 0.05.The mean pain score decreased from 5.93 ± 1.28 before intervention to 2.87 ± 1.12 after massage therapy. Statistical analysis showed a significant reduction in pain intensity (p = 0.001).Massage therapy is effective in reducing low back pain among pregnant women and may serve as a safe complementary therapy during pregnancy. Keywords: Massage Therapy, Low Back Pain, Pregnancy, Complementary Therapy, Pregnant Women.